Dari Infleksi hingga Komposisi: Manifestasi Kesadaran Morfologis Anak dalam Pembentukan Kata Bahasa Inggris di Dunia Virtual - Prihandini, Asih; Syava Nuraisyah, Mutia; Nugraha, Novian Denny; Nuraisyah, Mutia (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2025)
This study aims to explain how inflection, derivation, and compounding function as manifestations of children’s morphological awareness in English word formation within virtual environments. Online games such as Roblox, Minecraft, and Stumble Guys provide a natural space where children not only play but also experiment with linguistic forms. In this context, the development of morphological awareness is understood as children’s ability to consciously recognize, understand, and use word structures—from simple inflectional forms to complex morphological constructions. The research employed morphological content analysis within a descriptive qualitative approach. Data were obtained from transcripts of online game interactions among Indonesian children aged 7–10, which were recorded and categorized according to word-formation processes (inflection, derivation, and compounding). The analysis traced the development of children’s morphological awareness from the recognition stage (form identification) to the use stage (productive application). The findings indicate that children’s morphological awareness develops gradually. The initial stage is marked by recognition of inflectional forms such as loading, winning, and played, often produced through imitation of the game interface. At the intermediate stage, children exhibit derivative understanding through forms like legendary, respawned, and upgrading, reflecting a growing awareness of morphemic function. The advanced stage shows compositional creativity with forms such as bedwars, auto-clicker, and block dash, demonstrating an ability to construct new meanings creatively. These results confirm that the virtual world serves as a natural linguistic laboratory, facilitating the development of children’s morphological awareness from simple to complex forms through repeated and meaningful digital play experiences. Keywords: Inflection, Derivation, Morphological Awareness, Children, Online games